Assessment of polycyclic aromatic hydrocarbons in indoor and outdoor air of preschool environments (3–5 years old children). (January 2016) - Oliveira, Marta; Slezakova, Klara; Delerue-Matos, Cristina; Pereira, Maria do Carmo; Morais, Simone
Abstract: This work characterizes levels of polycyclic aromatic hydrocarbons (PAHs) in indoor and outdoor air of preschool environments, and assesses the respective risks for 3–5-years old children. Eighteen gaseous and particulate (PM1 and PM2.5 ) PAHs were collected indoors and outdoors during 63 days at preschools in Portugal. Gaseous PAHs accounted for 94–98% of total concentration (ΣPAHs ). PAHs with 5–6 rings were predominantly found in PM1 (54–74% particulate ΣPAHs ). Lighter PAHs originated mainly from indoor sources whereas congeners with 4–6 rings resulted mostly from outdoor emissions penetration (motor vehicle, fuel burning). Total cancer risks of children were negligible according to USEPA, but exceeded (8–13 times) WHO health-based guideline. Carcinogenic risks due to indoor exposure were higher than for outdoors (4–18 times). Highlights: Lighter PAHs originate from indoor sources, 4–6 rings PAHs result from outdoors. Gaseous PAHs account for the majority of PAH content in indoor air of preschools. Lifetime lung cancer risk values exceed WHO health-based guideline level of 10 −5 . Carcinogenic risks due to preschool indoor exposure are higher than for outdoors. Abstract : This work fills gap providing information on levels, phase distribution (gas, PM1, PM2.5 ) and risks of polycyclic aromatic hydrocarbons in indoor and outdoor air of preschool settings.